Learn To be Wise in Making Decision Through Studying Financial Mathematics - Ramadhan, M. Hasbi; Zulkardi; Putri, Ratu Ilma Indra; Resti, Yulia (Jurnal Pendidikan Matematika RAFA, 2024)
In everyday life, we were asked to be careful in making decisions, especially regarding financial matters. This research aimed to design a financial mathematical task to train students to be wiser in making decisions regarding financial matters. The method used in this research was design research with type of development studies. The approach used in this research was Realistic Mathematics Education (RME) or in Indonesia is better known as Pendidikan Matematika Realistik Indonesia (PMRI). For the context, this research used buying a house with credit or banking context. This research was conducted at Vocational High School 01 Jambi City with the subjects were eleventh-grade students with major of accounting. This research produced a financial mathematical task in the context of buying a house that was valid, practical, and has potential effect for financial mathematics learning. The research results also found that students became wiser in making decisions regarding financial matters. This research can also be a reference for vocational high school teachers to make financial mathematics teaching materials.